Effect of Characteristic Impedance in Estimating Specific Energy and Average Fragment Size at High Strain Rates of Some Peridotitic Rock Materials at Laboratory Scale - Toochukwu Ozoji; Zong-Xian Zhang; Aladejare Adeyemi; Yang Qiao; Li-Yuang Chi (Rock Mechanics and Rock Engineering, 2023)
In this study, the application of characteristic impedance in estimating specific energy and average fragment size of rocks was investigated during rock breakage at high strain rates. To achieve this, rock specimen was prepared in accordance with recommendations of the International Society for Rock Mechanics and broken at high strain rates using the split Hopkinson’s pressure bar system. Results reveal that although strain rate is well related to specific energy and average fragment size of broken rocks, the product of characteristic impedance and strain rate is more reliable for estimating the forementioned parameters. In addition, strain rate and dissipated energy generally increase at higher incident energies while the average fragment size of broken rocks reduces at higher strain rates. Based on these findings, more studies on indirect estimation of energy requirement for rock breakage to desired average fragment sizes is recommended from the product of characteristic impedance and strain rate.